Keterbatasan Rapid Test dalam Deteksi HIV Dini: Perbandingan dengan Metode ECLIA pada Sampel Donor - Resmi Aini; Adira Padmarini (Nusantara Sehat: Jurnal Kesehatan Indonesia, 2026)
Background: Blood transfusion safety depends on the ability of screening methods to detect transfusion-transmitted infections (TTIs), including human immunodeficiency virus (HIV). Rapid tests are widely used because they are practical and economical; however, they have limitations in detecting HIV infection during the early stage due to the window period. Electrochemiluminescence immunoassay (ECLIA), a fourth-generation method, can simultaneously detect HIV antibodies and p24 antigen, thereby potentially improving early HIV detection. Objective: This study aimed to analyze the limitations of rapid tests compared with ECLIA in HIV screening among blood donors. Methods: This study used a retrospective descriptive comparative design based on HIV screening data from blood donors at the Indonesian Red Cross Blood Donation Unit in Yogyakarta. Rapid test results were compared with ECLIA results as the reference method and analyzed based on sensitivity, specificity, predictive values, and diagnostic accuracy. Results: ECLIA showed higher sensitivity than rapid tests, particularly during the early stage of infection. Rapid tests may produce false-negative results because of their limited detection ability during the window period, whereas both methods demonstrated relatively high specificity. Conclusion: ECLIA has better diagnostic performance than rapid tests for HIV screening among blood donors. Fourth-generation methods are recommended to improve blood transfusion safety through earlier HIV detection.   Keywords: ECLIA; HIV; rapid test